Project on Human Development in Chicago Neighborhoods (PHDCN): Forward Memory, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Forward Memory instrument. It was taken from the attention and memory battery of the Leiter International Performance Scale, and it assessed cognitive function in subjects by measuring visuospatial memory. It was administered to subjects in Cohort 0.